2014
DOI: 10.1080/10962247.2014.1001500
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory hospitalizations in association with fine PM and its components in New York State

Abstract: Despite observed geographic and temporal variation in particulate matter (PM)-related health morbidities, only a small number of epidemiologic studies have evaluated the relation between PM 2.5 chemical constituents and respiratory disease. Most assessments are limited by inadequate spatial and temporal resolution of ambient PM measurements and/or by their approaches to examine the role of specific PM components on health outcomes. In a case-crossover analysis using daily average ambient PM 2.5 total mass and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…To date, the role of specific chemical constituents on PM-induced airway inflammation is limited (Jones et al, 2015). For example, Delfino et al (Delfino et al, 2013) found that ambient EC and OC were significantly associated with FeNO in a pediatric asthma panel.…”
Section: Discussionmentioning
confidence: 98%
“…To date, the role of specific chemical constituents on PM-induced airway inflammation is limited (Jones et al, 2015). For example, Delfino et al (Delfino et al, 2013) found that ambient EC and OC were significantly associated with FeNO in a pediatric asthma panel.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Nakhle et al (20) indicated that the concentrations of PM 10 and PM 2.5 were positively related to respiratory and circulatory system disease admissions in Beriut, Lebanon. Jones et al (21) indicated that PM 2.5 concentrations were positively related to respiratory hospitalizations in New York. However, most previous studies have focused only on the effects of PM 2.5 (22).…”
Section: Introductionmentioning
confidence: 99%
“…Of the range of atmospheric pollutants, particulate matter-especially PM2.5 (particulate matter 2.5 microns diameter or less)-has the most serious effects on health (Atkinson et al, 2015;Cohen et al, 2005;Franck et al, 2011;Fuzzi et al, 2015;Jones et al, 2015), although it is acknowledged that the particulate matter health association is complex and wrought with a number of toxicological puzzles (Maynard, 2015). An important constituent of the PM2.5 mix is organic aerosol (OA).…”
Section: Air Qualitymentioning
confidence: 99%